PREVALENCE OF LEFT VENTRICULAR HYPERTROPHY IN NEWLY DIAGNOSED HYPERTENSIVE PATIENTS - Masood, Umair; Javed, Ali; Ashraf, Fariha; Javed, Umar; Siddique, Abdul Wahab; Zaheer, Qasim (Pakistan Armed Forces Medical Journal, 2020)
Objective: To detect frequency of left ventricular hypertrophy in patients with newly diagnosed hypertension. Study Design: Cross sectional study. Place and Duration of Study: Out patient and inpatient, Department of Medicine of Combined Military Hospital Nowshera, from Sep 2018 to Sep 2019. Methodology: One hundred and twenty patients were included in this study and they were classified into stage 1 and 2 hypertension according to American college of cardiology guidelines. Electrocardiography of all patients was done and Sokolow-Lyon and Cornell voltage criteria were used to detect left ventricular hypertrophy (LVH). 2-D echocardiography was also done to confirm the presence or absence of left ventricular hypertrophy. Results: Amongst 120 patients 71 (59.16%) were males and 49 (40.83%) were females with mean age 47.79 ± 0.79 years. There was no significant gender based relationship. In this study 41 (34.16%) patients had stage 1 hypertension whereas 79 (65.83%) had stage 2 hypertension at time of diagnosis. Sokolow-Lyon criteria showed 21 (17.5%) patients had left ventricular hypertrophy, 17 (14.6%) patients had left ventricular hypertrophy as per Cornell Voltage criteria with an overlap of 9 (7.5%). Echocardiography revealed left ventricular hypertrophy in 28 (23.33%) patients amongst which 24 had Stage 2 hypertension and 4 had Stage 1 hypertension (p<0.05). Conclusion: Significant number of patients with newly diagnosed hypertension already had left ventricular hypertrophy due to lack of screening and education.